Analisis Perubahan Tekanan Udara Perangkat Oscillating Water Column dengan Metode phi-Buchingham - Kasi, Paulinus Sargius; Jasron, Jahirwan Ut; Gurnawati, Gurnawati (Universitas Nusa Cendana, 2023)
ABSTRACT The increase in human population along with the times and technology must be increasingly difficult to separate from energy needs, one of which is the need for electrical energy. One source of energy that has not been widely utilized is ocean wave energy. Ocean wave power plants basically have a working principle, namely converting ocean wave energy (mechanical energy) into electrical energy. One of the wave energy conversion system technologies is the Oscillating water column (OWC) technology. Technology Oscillating Water Coloumn this, using the air pressure from the watertight chamber to movewells turbine This turbine will then be used to generate electricity. Forms of studies that can be carried out to study the phenomenon of changes in device air pressure Oscillating Water Coloumn is mathematical modeling. One of the mathematical modeling can be done by phi-Buchingham. Using Buckingham's Pi theorem dimensional analysis can make it easier to analyze and make experimental steps faster and more focused. Keywords: Ocean waves, Oscillating Water Coloumn (OWC), Barometric pressure, phi-Buchingham